Smart materials and the influence of atom sizes on martensite microstructures in copper-based shape memory alloys - Adiguzel, O. (Elsevier Science Sa, 2007)
A series of alloy systems exhibit a peculiar property which involves the repeated recovery of macroscopic shape of material at different temperatures. The study of such materials, which are often called smart materials due to their capacity of responding to changes in the environment, is a field of research in rapid evolution. The origin of this phenomenon lies in the fact that the material changes its internal crystalline structure with changing temperature. Copper-based beta-phase alloys are widely used as a shape memory component in devices. On cooling from high temperature, these alloys undergo a displacive transition which has a close packed-structure following two ordering transitions. This transition is called martensitic transition and responsible for the shape memory effect. The martensitic structures in beta-phase alloys are closely related to the austenitic structures and inherit the order in the parent phase due to the displacive character of transition. In case these alloys are deformed in a temperature range in martensitic condition they change in shape and recover the undeformed original austenitic shape on heating over the reverse transition temperature after removing the strain. These materials regain the deformed shape on cooling to the martensitic state and cycle between deformed and undeformed shapes on cooling and heating. Therefore, this property is called reversible shape memory effect. The {110}(beta) type plane of parent which is the basal plane for martensite is subjected to the hexagonal distortion with martensite formation on which atom sizes have important effect. In case the atoms occupying the lattice sites have the same size, the hexagon becomes regular hexagon otherwise the hexagon undergoes a distortion in case atom sizes are different. Due to this distortion, the spacing differences, Delta d, between particularly selected pairs of diffraction planes providing a special relation between miller indices become different zero and can be a measure of the ordering degree in martensite. The decrease in spacing difference leads to disordering in martensite. (c) 2006 Published by Elsevier B.V.
3rd International Conference on Advanced Manufacturing Technology (ICMAT) -- MAY, 2004 -- Kuala Lumpur, MALAYSIA
Keywords: smart materials; shape memory effect; martensite; beta-phase alloys; ordered structures; hexagonal distortion